Lesotho’s Garment Exports : Attracting Foreign Direct Investment - Riley, Thyra (World Bank, Washington, DC, 2012)
Lesotho has built a small but significant manufacturing sector, representing about 18 percent of gross domestic product (GDP). During the past decade, the sector has increased 14-fold, an exceptional achievement by African standards. This growth was due largely to an export boom of ready-made garments and footwear fueled by foreign investors coming principally from the Republic of South Africa and Asia. Lesotho's success in attracting export oriented foreign direct investment was due primarily to Lesotho's comparative advantage with respect to productive labor and favorable trade arrangements. These advantages were supported and enhanced by a World Bank project which reduced the costs and risks of investment through a policy reform package, the financing of industrial infrastructure, and the establishment of an investment promotion institution and strategy to market the country as an attractive investment site.